From Oral to Written Da’wah: A Study on the Development of Preaching Methods in Indonesia - Safei, Agus Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Musabaqah Tilawatil Qurân (MTQ) is derived from Arabic by Indonesian society to refer to the literary Qurânic Recitation Competition. This is a large and fundamental development in the preaching and teaching of Islam in Indonesia. It started in the 1940s and was nationalized in the 1960s to help promote the power way of reading and reciting the Qurân . Since its nationalization in 1968, MTQ has become a tradition for Indonesians, although Qurânic recitation itself is a common practice and a universal activity within the Muslim world. During Qurânic recital competitions, participants compete in a number of different elements, which include Tilawah (the art of reciting the Quran), Fahm Al-Qurân (comprehension of Qurânic content), and tahfiz Qurân (memorization of the Qurân ). In 2003, a new field was added to the MTQ competition, i.e.,Musabaqah Makalah Ilmiah Al-Qurân (M2IQ), which is translated as Al-Qurânic Academic Writing Competition. Since its first appearance during the 2003 Regional MTQ in the West Java Province, and later during the 2008 National MTQ, M2IQ, which is basically written da’wah material, has been considered an innovation within the preaching field in Indonesia. In the past, Islamic preaching (da’wah) in Indonesia has always been in the oral form. This development calls for comprehensive study to understand the underlying principles within the emerging M2IQ approach in the teaching of Islam or the Qurân within Indonesia, and its contribution to the shaping of modern Islamic preaching or teaching in Indonesia.